First-line disease-modifying drugs in relapsing–remitting multiple sclerosis: an Italian real-life multicenter study on persistence. (3rd October 2018) - Ferraro, Diana; Camera, Valentina; Baldi, Eleonora; Vacchiano, Veria; Curti, Erica; Guareschi, Angelica; Malagù, Susanna; Montepietra, Sara; Strumia, Silvia; Santangelo, Mario; Caniatti, Luisa; Foschi, Matteo; et al.
Abstract: Objective: The introduction of oral disease-modifying drugs (DMDs) in addition to the available, injectable, ones for relapsing–remitting multiple sclerosis (RRMS) could be expected to improve medication persistence due to a greater acceptability of the route of administration. The aim of the study was to compare the proportion of patients discontinuing injectable DMDs (interferon beta 1a/1b, pegylated interferon, glatiramer acetate) with those discontinuing oral DMDs (dimethylfumarate and teriflunomide) during an observation period of at least 12 months. Secondary aims were to compare the time to discontinuation and the reasons for discontinuation between the two groups and to explore the demographic and clinical factors associated with DMD discontinuation. Methods: In this prospective, multi-center, real-life observational study, patients commencing any first-line DMD between 1 January 2015 and 31 July 2016 were enrolled and followed up for at least 12 months or until the drug was discontinued. Results: Of the 520 included patients, 262 (49.6%) started an injectable and 258 (50.4%) an oral DMD. There was no difference in the proportion of patients on oral ( n = 62, 24%) or on injectable ( n = 60, 23%) DMDs discontinuing treatment, the most frequent reason being adverse events/side-effects. Higher baseline Expanded Disability Status Scale (EDSS) scores and younger age increased the odds of treatment withdrawal. Time to treatment discontinuation was not different between the two groups and was not influenced by the initiated DMD (oral versus injectable), even after adjustment for baseline differences. Conclusion: The route of administration alone (i.e. oral versus injectable) was not a significant predictor of persistence with first-line DMDs in RRMS.